Course of Grip Force Impairment in Patients With Early Rheumatoid Arthritis Over the First Five Years After Diagnosis. Issue 4 (11th March 2018) - Rydholm, Maria; Book, Christina; Wikström, Ingegerd; Jacobsson, Lennart; Turesson, Carl
Abstract : Objective: Objective measures of function are important in rheumatoid arthritis (RA). The objective of this study was to investigate grip strength in patients with early RA. Methods: An inception cohort of 225 patients with early RA was followed in accordance with a structured protocol. Average and peak grip force values of the dominant hand (measured using a Grippit device [AB Detektor]) were evaluated and compared to expected age‐ and sex‐specific reference values from the literature. Separate analyses were performed for those with limited self‐reported disability (Health Assessment Questionnaire disability index [HAQ DI] score ≤0.5) and clinical remission (Disease Activity Score in 28 joints <2.6). Results: Baseline average grip force among RA patients was significantly lower than the corresponding expected value (mean 105N versus 266N; P < 0.001). Observed average and peak grip force values were significantly reduced compared to those expected in women as well as in men over time and at all time points. The average grip force improved significantly from inclusion to the 12‐month visit (age‐corrected mean change 34N [95% confidence interval 26–43]). At 5 years, the average grip force was still lower than that expected overall (mean 139N versus 244N; P < 0.001), and also among those with HAQ DI scores ≤0.5 and those in clinical remission. Conclusion: Grip strength improved in early RA patients, particularly during the first year. However, it was still significantly impaired 5 years after diagnosis, even among those with limited self‐reported disability and those in clinical remission. This suggests that further efforts to improve hand function are important in early RA.